International encyclopedia of the social sciences - International... (The Macmillan Company & The Free Press, 1968)
tr, jil.3-4=c.1-2; jil.5-6=c.1-2; jil. 7-8=c.1; jil.15-17, index=c.1/oen, jil.11-12, 13-14=c.1/stoc6, jil.3-4=c.1-2; jil.5-6=c.1-2; jil. 7-8=c.1; jil.11-12=c.1; jil.15-17, index=c.1-2